Solar radio burst in National Space Agency of Malaysia (ANGKASA). (January 2019) - Nadirah Ishak, Asnor; Zulaikha Mohd Afandi, Nur; Umar, Roslan; Hazmin Sabri, Nor; Mohd Radzi, Zahira; Juraiza Ishak, Asnor; Anwar, Radial
Abstract: The sun is an active star that produces large-scale energetic events, such as solar flares and coronal mass ejections (CMEs). These phenomena are observable across the electromagnetic spectrum, from gamma rays at hundreds of MeV to radio waves with wavelengths of tens of metres. Solar flares and CMEs can excite plasma oscillations which can emit radiation at metric and decametric wavelengths. These radio bursts are classified in five main types. This paper gives a solar radio burst type III (16 July 2017) in National Space Agency (ANGKASA), Banting, Selangor, Malaysia. Compact Astronomical Low-Cost Instrument for Spectroscopy in Transportable Observatories (CALLISTO) is used in this system to observe solar radio activities. The main applications for this CALLISTO is to observe a solar radio bursts and radio frequency interference (RFI) monitoring for astronomical science, education and outreach. The CALLISTO natively operates between 45MHz to 870MHz and its observed daily.